Specificity and features of the development of aesthetics in the Ukrainian soviet philosophy in the 50–60s of the XX century - V. E. Turenko; N. V. Yarmolitska (Ukrainian Cultural Studies, 2021)
The article highlights the specificity of research in the field of aesthetics in the context of the development of Soviet philosophy in Ukraine in the 50-60s. XX century. There are three main vectors of scientific work: ideological works, original aesthetic developments and historical and aesthetic research. It is revealed that ideological aesthetic works were based on the concept of "positive aesthetics" by A. Lunacharsky, which contributed to the development of the concept of socialist realism, nationality of art by Ukrainian Soviet thinkers, as well as criticism of Western aesthetics and the approval of "Soviet aesthetics". It is shown that, unlike specifically ideological works, the original aesthetic developments were aimed not at substantiating certain provisions of Marxist-Leninist philosophy, but, as far as possible, creating new concepts and ideas in this branch of philosophical knowledge. It was revealed that in the context of historical and aesthetic research, in contrast to Russian researchers, Ukrainian scientists focused mainly on the development of the national tradition. It is proved that during the period under study, aesthetic problems, along with logic, methodology of science, philosophical problems of natural science, were one of the leading in Soviet Ukraine, thereby being one of its centers throughout the Soviet Union.